Insurgency : how Republicans lost their party and got everything they ever wanted - Peters, Jeremy (Jeremy W.) (Crown, 2022)
"How, Peters asks, did conservative values that Republicans claimed to cherish, like small government, fiscal responsibility, and morality in public service, get completely eroded as an unshakable faith in Donald Trump grew to define the party? The answer is a tale traced across three decades--with new reporting and firsthand accounts from the people who were there--of populist uprisings that destabilized the party ... After Barack Obama's election convinced many Republicans that they faced an existential demographics crossroads, many believed the only way to save the party was to create a more inclusive and diverse coalition. But party leaders underestimated the energy and popular appeal of those who would pull the party in the opposite direction ... In this sweeping history, Peters details key junctures and episodes to unfurl the story of a revolution from within. Its architects had little interest in the America of the new century but a deep understanding of the iron will of a shrinking minority"--